Ferroelectric polarization and iron substitution synergistically boost electrocatalytic oxygen evolution reaction in bismuth oxychloride nanosheets - Singh, Dinesh; Joshi, Bhavana; Poddar, Pankaj (Langmuir, 2023)
Ferroelectric materials have gained significant interestin variouskinds of water splitting, but the study of ferroelectric materialsfor electrocatalytic water splitting is in its infancy. Ferroelectricmaterials have spontaneous polarization below their Curie temperaturedue to dipolar alignment, which results in surface charges. In 2Dferroelectric materials, spontaneous polarization depends on thickness.Herein, we report that thickness-dependent ferroelectric polarizationin 2D nanosheets can also accelerate the oxygen evolution reaction(OER) along with the tailored active surface area of exposed crystallinefacets, which improves the electrocatalytic activity relatively. Iron-substitutedBiOCl nanosheets of varying thickness are fabricated by varying thepH using a facile coprecipitation method. The substituted iron enhancespolarization and electrochemical active sites on the surface. Thefindings in this study show that the exposed (001) facet and higherthickness of the nanosheets have high ferroelectric polarization and,in turn, superior electrocatalytic activity and remarkable stability,requiring low overpotentials (348 mV and 270 mV at 100 mA/cm(2) and 10 mA/cm(2)) in alkaline (1.0 M KOH) electrolyte. Asthe thickness of the nanosheets is decreased from 140 to 34 nm, theelectrocatalytic performance of iron-substituted BiOCl nanosheetsstarts to reduce due to the lower Coulomb-Coulomb interactionand the increasing depolarization.

Scalable synthesis of dodecanethiol-capped bismuth nanoparticles by a solvent-free solid-state grinding method for reduction of 4-nitrophenol to 4-aminophenol - Singh, Dinesh; Poddar, Pankaj (Langmuir, 2023)
Thiol-capped metal nanoparticles have two constituents:an inorganicmetal and an organic molecule as a shell. Both characters are inbuiltin the structure of the metal thiolate. Herein, we have investigatedbismuth dodecanethiolate as a precursor for the synthesis of dodecanethiol-cappedbismuth nanoparticles (Bi NPs) by a solid-state grinding method. Byusing sodium borohydride and bismuth dodecanethiolate, crystallinebismuth nanoparticles are synthesized in a solvent-free environmentat room temperature (24 & PLUSMN; 4 & DEG;C). Bi NPs are tested for catalyticactivity by reducing 4-nitrophenol (4-NP) to 4-aminophenol (4-AP)with an excess of NaBH4. Dodecanethiol-capped bismuth nanoparticlesexhibit an efficient reduction of 4-NP to 4-AP within 12 min. Additionally,these nanoparticles remain catalytically active for up to three cycles.

In situ synthesis of metal (Bi0)-semiconductor [BiOX (X = Cl, Br, and I)] nanocomposites as a highly effective catalyst for the reduction of 4-nitrophenol to 4-aminophenol - Singh, Dinesh; Poddar, Pankaj (New Journal of Chemistry, 2024)
The reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) has been efficiently catalyzed by in situ generated Bi-0-BiOX (X = Cl, Br, I) nanocomposites in the presence of sodium borohydride (NaBH4). The hierarchical 3D arrays of precursors (BiOCl, BiOBr, and BiOI) have been synthesized by a facile co-precipitation method at ambient temperature. The metallic Bi-0 is generated in situ by partial reduction of the Bi3+ ions in BiOX (X = Cl, Br, and I) mediated by NaBH4 during the conversion of 4-NP to 4-AP. In situ generated Bi-0-BiOX shows better catalytic activity than Bi-0-BiOX composite formed by mixing individually synthesized metallic Bi-0 particles with semiconducting BiOX nanoparticles. The Bi-0-BiOI nanocomposite demonstrated higher catalytic activity (k(app) = 0.529 min(-1)) compared to Bi-0-BiOCl (k(app) = 0.095 min(-1)) and Bi-0-BiOBr (k(app) = 0.098 min(-1)) due to its efficient conversion into metallic Bi-0. The approximate percentage composition of in situ generated metallic Bi-0 on the surface of BiOCl, BiOBr, and BiOI is nearly 10, 17, and 25%, respectively. Further, the reduction of 4-NP has been completed within 24, 22, and 6 minutes by in situ generated Bi-0-BiOCl, Bi-0-BiOBr, and Bi-0-BiOI nanocomposites from BiOCl, BiOBr, and BiOI, respectively. Extensive studies have been conducted to generate a better understanding of the actual catalytic sites present on the surface of the catalysts.

An in-depth study of the Fe-Se system at the nanoscale reveals remarkable results on the electrocatalytic oxygen evolution reaction - Singh, Dinesh; Ghalawat, Monika; Poddar, Pankaj (European Journal of Inorganic Chemistry, 2025)
A catalyst for an electrocatalytic oxygen evolution reaction (OER) is a key component of the large-scale storage of renewable energy through the conversion of water into oxygen and hydrogen. Iron-based selenide materials are currently being considered as potential options for electrocatalytic oxygen evolution reaction (OER) because of their, widespread availability, low cost, and outstanding performance. In this study, we employed a thermal decomposition method to synthesize all stable phases of the Fe-Se system, including Fe7Se8, Fe3Se4, FeSe2, and FeSe. Additionally, we slurry-coated these phases onto a three-dimensional (3D) nickel foam substrate. The prepared 3D electrodes of Fe7Se8, Fe3Se4, FeSe2, and FeSe exhibit remarkably low overpotentials of 270, 276, 299, and 289 mV at a current density of 50 mA/cm2 for OER. In addition, the catalytic activity for OER is also tested on glassy carbon electrodes to compare its performance with the Ni-foam 3D substrate. The Fe7Se8 phase in the Fe-Se system exhibits the highest catalytic activity towards OER on both substrates due to variations in the Fe2+/Fe3+ ratio and the presence of Fe vacancies (cation vacancies) within the crystal lattice. Moreover, a faradaic efficiency of 98 % was exhibited by Fe7Se8 for the oxygen evolution reaction (OER).
Keywords: Iron selenide system; OER electrocatalyst; Thermal decomposition method

Study of magnetism and electrocatalytic properties in perovskite DyCrO3 - Ughade, Supriya; Singh, Dinesh; Poddar, Pankaj (Journal of Alloys and Compounds, 2025)
Uniformly sized perovskite DyCrO3 was synthesized by facile hydrothermal method. Complex interdependence of various parameters such as - pH, crystal growth duration, reaction temperature, precursor, and capping molecules on crystal growth was extensively investigated. The effect of synthesis parameters on the magnetic properties of hydrothermally synthesized DyCrO3 was compared with high-temperature synthesized DyCrO3. DyCrO3's potential for electrocatalytic water splitting in an alkaline medium (1.0 M KOH) was also evaluated. It demonstrates an overpotential of 280 mV for oxygen evolution reaction (OER) and 210 mV for hydrogen evolution reaction (HER). Further, it exhibits promising stability for OER and HER.
Keywords: DyCrO3; Electrocatalytic water splitting; Hydrothermal synthesis; magnetic property; perovskite

Hierarchical 3D Fe-doped Bi2MoO6 arrays supported on a Ni foam: an effective electrocatalyst for alkaline water splitting - Singh, Dinesh; Poddar, Pankaj (Nanoscale, 2026)
Electrocatalytic water splitting is a viable route to sustainable hydrogen generation; however, designing high-performance, stable catalysts remains a considerable challenge. Bismuth-based materials have not yet been well studied for electrocatalytic alkaline water splitting, despite their favourable electronic structure and chemical stability. Here, iron-doped hierarchical three-dimensional (3D) Bi2MoO6 arrays have been grown in situ on a 3D conductive nickel foam (NF) substrate using a facile solvothermal method. The optimal Fe-doped Bi2MoO6/NF (Fe, 5 mol% substituting Bi) or BMOF-5 electrocatalyst exhibits excellent electrocatalytic activity towards the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in alkaline media (pH similar to 14.0) owing to abundant active sites in the hierarchical 3D framework, high electrical conductivity, and superhydrophilic nature. At a current density of 10 mA cm-2, the BMOF-5 electrocatalyst requires 262 mV and 153 mV overpotentials for the OER and HER, respectively. In addition, a potential of 1.62 V is required by the BMOF-5/NF parallel to BMOF-5/NF cell at a current density of 10 mA cm-2 for overall water splitting. The BMOF-5/NF electrocatalyst shows durability of 24 h and 22 h for the HER and OER in a 1 M KOH electrolyte at current densities of 100 and 10 mA cm-2, respectively. In this study, a small amount of iron plays an important role in altering the electronic environment of Bi2MoO6, increasing the electrochemically active sites and reducing the charge-transfer resistance at the electrode-electrolyte interface. In addition, this work presents an easy and efficient approach to enhance the electrocatalytic performance of Bi2MoO6, which is of significant practical importance.

Tuning the electric dipole transitions (5D0 → 7F2 and 5D0 → 7F4) in thin Eu-doped BiOCl nanosheets - Singh, Dinesh; Poddar, Pankaj (Journal of Physical Chemistry C, 2026)
The polarization and depolarization of layered ferroelectric materials can be tuned by altering the thickness of nanosheets, apart from controlling inter/intralayer distances, doping of ions, the surrounding dielectric environment, etc. In two-dimensional, single-crystalline ferroelectric nanosheets, the reduction in the thickness facilitates the internal electric field (IEF), which leads to enhanced depolarization. BiOCl is a layered ferroelectric material with repeating layers of [Bi2O2](2+), which exhibit anisotropy. However, the depolarization and polarization of BiOCl are significantly influenced by the thicknesses of its nanosheets. Herein, 1-dodecanethiol-capped europium (Eu3+)-doped BiOCl thin nanosheets resembling a two-dimensional structure have been synthesized using the solid-state grinding method at ambient temperature. As a result of the depolarization effect, the strength of the electric dipole transitions D-5(0) -> F-7(2) and D-5(0) -> F-7(4) increases in the Eu-doped BiOCl nanosheets. However, thiol capping helps in synthesizing uniform 2D nanosheets with reduced vertical dimensions (thickness near 15-30 nm). It is observed that all of the prepared samples with varying Eu ion concentrations show uniform nanosheet-like morphology, as confirmed by electron microscopy (FESEM and HRTEM). As the concentration of Eu ions increases in the BiOCl host lattice, the intensity of electric dipole transitions also increases (until 9 mol %). Fourier transform infrared spectroscopy (FT-IR) reveals the coating of 1-dodecanthiol on the Eu-doped BiOCl molecule. Furthermore, the Eu-doped BiOCl samples showed prominent far-red emission at 700 nm, corresponding to the D-5(0) -> F-7(4) transition. Moreover, this work emphasizes the synthesis of Eu-doped phosphor at an ambient temperature of 24 +/- 2 degrees C and generates a deeper understanding of the abnormal electric dipole (D-5(0) -> F-7(4)) transition.